AUDITOR SYARIAH APAKAH CUKUP DENGAN SERTIFIKASI AKUNTANSI SYARIAH? - Liva Fatrianda; Shabrina Syifa Qolbiyah; Zalfa, Salma Rodliyatu (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2024)
The purpose of this research is to present the view that accounting certification alone is insufficient for the practice of Islamic auditors. With this rationale, the article employs the Systematic Literature Review (SLR) method to further investigate related issues. The findings of this research indicate that the lack of dedicated education institutions and certifications for Sharia auditors in Indonesia is a key reason why the competence of Sharia auditors is still in doubt. The Sharia accounting certification provided by the Indonesian Institute of Accountants is limited to the technical aspects of accounting and does not encompass Sharia audit aspects. Therefore, additional certification focusing on Sharia audit competence is deemed necessary.